Jeden z herezjarchów? Przedstawienia ikonograficzne Mahometa w rękopisie Рнб, f.IV.151 w kontekście staroruskich narracji na jego temat - Brzozowska, Zofia (Vox Patrum, 2018)
The РНБ, F.IV.151 manuscript is the third volume of a richly illustrated historiographical compilation (so-called Лицевой летописный свод – Illustrated Chronicle of Ivan the Terrible), which was prepared in one copy for tsar Ivan IV the Terrible in 1568-1576 and represents the development of the Russian state on the broad background of universal history. The aforementioned manuscript, which contains a description of the history of the Roman Empire and then the Byzantine Empire between the seventies of the 1st century A.D and 919, includes also an extensive sequence devoted to Muhammad (Ѡ Бохмите еретицѣ), derived from the Old Church Slavonic translation of the chronicle by George the Monk (Hamartolus). It is accompanied by two miniatures showing the representation of the founder of Islam. He was shown in an almost identical manner as the creators of earlier heterodox trends, such as Arius or Nestorius. These images therefore become a part of the tendency to perceive Muhammad as a heresiarch, a false prophet, and the religion he created as one of the heresies within Christianity, which is also typical of the Old Russian literature.